(1→3)-β-d-Glucan: A Biomarker for Microbial Translocation in Individuals with Acute or Early HIV Infection? - Hoenigl, Martin; Pérez-Santiago, Josué; Nakazawa, Masato; de Oliveira, Michelli Faria; Zhang, Yonglong; Finkelman, Malcolm A.; Letendre, Scott; Smith, Davey; Gianella, Sara (Frontiers in Immunology, 2016)
Background: The extent of gut microbial translocation, which plays roles in HIV disease progression and non-AIDS comorbidities, appears to vary with the composition of the gut microbiome, particularly the presence of Lactobacillales, which reduce mucosal injury. While low proportions of Lactobacillales in the distal gut microbiome are a very promising indicator of microbial translocation, measurement is expensive and complicated and not feasible for clinical routine. (1→3)-β-D-Glucan (BDG) is a component of most fungal cell walls and might be a surrogate marker for Lactobacillales proportion in the gut and a useful indicator of HIV-associated gut injury. This study evaluated BDG as a biomarker of gut integrity in adults with acute or early HIV infection (AEH). Methods: Study samples were collected longitudinally during study visits at weeks 0, 12, and 24 in a cohort of 11 HIV-infected men starting antiretroviral therapy during AEH. Blood plasma levels of BDG, soluble cluster of differentiation 14 (sCD14) and lipopolysaccharide (LPS) were measured and then correlated with the proportion of Lactobacillales in the distal gut microbiome, as measured by 16s rDNA sequencing by using mixed-effects models with random intercepts. Results: Mean BDG and sCD14 levels across subjects were associated with Lactobacillales after controlling for time effects and within-subjects correlations (p-values<0.05), while LPS levels were not. Specifically, each point increase in mean BDG and sCD14 levels across participants was associated with 0.31±0.14 and 0.03±0.01 point decrease in mean Lactobacillales proportions, respectively. Conclusions: BDG and sCD14 may be indicators of low Lactobacillales in the gut in adults with acute or early HIV infection, and serve as biomarkers of gut integrity and microbial translocation in HIV infection. Larger studies are needed to confirm our findings.